A comparative study of tranlation procedure tow ard /syahida/noun derivation found in english quran translation by taqiyuddin al-hilali & Muhsin Khan and marmaduke pickthall - Izzati Karimah (Fak. Adab dan Ilmu Budaya UIN Sunan Kalijaga, 2018)
yt 1./ws.c.1